Curcumin Reverses Cisplatin Resistance in NSCLC via Transcriptional Suppression of ABCB1 and Functional Inhibition of P-glycoprotein: A Mechanistic and Synergistic Analysis - Khairiel Anwar; Eduardo Michael Perez; Febria Suryani; Franklin Shane (HM Publisher, 2025)
Non-small cell lung cancer (NSCLC) remains the leading cause of cancer-related mortality globally. The efficacy of Cisplatin (DDP), a first-line chemotherapeutic, is frequently compromised by multidrug resistance (MDR), primarily driven by the overexpression of the ATP-binding cassette transporter P-glycoprotein (P-gp/ABCB1). Curcumin, a polyphenol with pleiotropic pharmacological effects, has shown potential as a chemosensitizer. This study aimed to rigorously quantify the synergistic interaction between Curcumin and Cisplatin and elucidate whether the reversal of resistance is mediated through functional blockade or genetic suppression of ABCB1. We utilized the human NSCLC cell line A549 and its stable, authenticated DDP-resistant counterpart (A549/DDP). Cytotoxicity was assessed using the CCK-8 assay with strict vehicle controls. Drug synergy was quantified using the Chou-Talalay Combination Index (CI) method. P-gp efflux function was evaluated by Rhodamine 123 (Rh123) accumulation, while apoptosis was analyzed via Annexin V-FITC/PI flow cytometry. The expression levels of P-gp and ABCB1 mRNA were determined by Western blotting and RT-qPCR, adhering to MIQE guidelines. A549/DDP cells exhibited a robust resistance phenotype (Resistance Index: 13.4). Co-treatment with non-toxic concentrations of Curcumin (20 μM) significantly reduced the IC50 of Cisplatin from 56.42 μM to 6.85 μM (p < 0.001), yielding a Reversal Fold of 8.2. The Combination Index was 0.45, indicating strong synergism. Curcumin treatment blocked P-gp-mediated efflux and, critically, downregulated ABCB1 mRNA by 72% and protein expression in a dose-dependent manner. This dual mechanism restored apoptotic sensitivity, increasing rates from 12.5% to 46.8%. In conclusion, curcumin effectively reverses Cisplatin resistance in NSCLC through a dual mechanism: immediate functional inhibition of the P-gp pump and delayed transcriptional repression of ABCB1. These findings support the development of Curcumin-based adjuvant therapies to overcome MDR.